PENGEMBANGAN LKPD BERBASIS MODEL INKUIRI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH DASAR - Rensi Esweti; Sry Apfani (Jurnal Riset Pendidikan Dasar Dan Karakter, 2025)
This study aimed to develop Student Worksheets (LKPD) based on an inquiry model to improve the critical thinking skills of fourth-grade elementary school students in science learning. This study uses the Research and Development (R&D) method with a 4-D model that includes define, design, develop, and disseminate. The research subjects consisted of 3 validators, 1 teacher, and 5 students. The research instruments were validation sheets, practicality questionnaires, and effectiveness tests. The results showed that the developed LKPD obtained a very valid level of validity with a design value of 93.75%, material 90%, language 95.83%, and lesson plan 86.25%. The results of practicality obtained a percentage of 91.66% with a very practical category, while effectiveness obtained an average of 92% with a very effective category. Thus, inquiry-based LKPD is suitable for use to improve the critical thinking skills of elementary school students.